THE EFFECT OF CUSTOMER VALUE AND CUSTOMER EXPERIENCE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AT CREATIVE INDUSTRY - Putri, Maghfirah Aginda; Kurniawan, Daniel (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
This study aims to examine how customer value and customer experience affect customer loyalty through customer satisfaction at Lokatara (PT Lokatara Karya Indonesia). The research variables include independent variables customer value and customer experience, an intervening variable customer satisfaction, and a dependent variable customer loyalty. The study employed a saturated sampling method, with 79 Lokatara customers as respondents. All hypotheses were tested using SEM-PLS analysis version 3.0. The results indicate that customer value has a positive and significant effect on customer satisfaction and customer loyalty, customer experience has a positive and significant effect on customer satisfaction and customer loyalty, and customer satisfaction has a positive and significant effect on customer loyalty. Additionally, customer satisfaction mediates the influence of customer value and customer experience on customer loyalty. The implication for Lokatara as a service company is that it can adopt a personalized approach to enhance customer experience.